2021
DOI: 10.1007/s42729-021-00502-3
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid– and Ascorbic Acid–Induced Salt Tolerance in Mung bean (Vigna radiata (L.) Wilczek) Accompanied by Oxidative Defense Mechanisms

Abstract: The present study aimed at investigating the physiochemical role of phytoprotectants, i.e., salicylic acid (SA) and ascorbic acid (AsA), to induce salt tolerance (0, 80 mM NaCl) in two indigenous mung bean varieties, viz. NM-92 (salt tolerant) and NM-28 (salt sensitive). The mung bean varieties were exposed to salinity stress (80 mM NaCl) after 1 week of germination and then exogenously sprayed with different levels of SA and AsA (0, 50, 100, 150 mg L −1 ) on appearance of stress symptoms. The experiment was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
7
6
0
Order By: Relevance
“…Figure 3 C,D show a clear trend of increasing ROS under salinity stress compared with the non-saline condition. A similar result was recorded by Nawaz et al [ 62 ], who found that salinity increased ROS levels in mungbean shoots. However, in this study, the application of SA and Kh retarded the production of H 2 O 2 under saline conditions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Figure 3 C,D show a clear trend of increasing ROS under salinity stress compared with the non-saline condition. A similar result was recorded by Nawaz et al [ 62 ], who found that salinity increased ROS levels in mungbean shoots. However, in this study, the application of SA and Kh retarded the production of H 2 O 2 under saline conditions.…”
Section: Discussionsupporting
confidence: 90%
“…The results in this study ( Figure 3 A) and those of previous studies indicate that SA application enhances the chlorophyll content of kidney bean plants [ 31 ], tomatoes [ 60 ], cucumbers [ 61 ], and mungbean [ 62 ]. These results could be due to the role of SA in increasing the relative vitality of photosynthesis and decreasing initial fluorescence [ 63 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, SA concentrations ranged from 0.83 to 4.16 mM. The application of low SA concentrations relieves the abiotic stress sensitivity in plants corroborating the data exhibited by NAWAZ et al (2021), whereas high concentrations (usually more than 1 mM) induced high levels of oxidative stress, leading to decreased abiotic stress tolerance and reduced growth (CHANDRA et al, 2007;MACHADO-NETO;DURÃES, 2006;MIURA;TADA, 2014).…”
Section: Salicylic Acid (Sa)supporting
confidence: 86%
“…According to BRILHANTE et al (2013), exogenous application of 0.85 mM AA to cowpea seeds [Vigna unguiculata (L.) Walp] 'Epace 10' after artificial ageing attenuated the deleterious effects on membrane integrity caused by artificial ageing and favoured the physiological quality of seeds. Similarly, Vigna radiata seeds submitted to treatment with AA (NAWAZ et al, 2021;ROYCHOUDHURY et al, 2016) increased their tolerance to environmental stress caused by salinity and cadmium toxicity. ---------------------------------------------------------------------Assay 1 -1 application of 12 mL.50 sprouts -1 - --------------------------------------------------------0 -----------------------------------------------------Assay 2 -2 applications of 12 mL.50 sprouts -1 - -------------------------------------------------------0 ----------------------------------------------------Assay 3 -2 applications of 6 mL.50 sprouts -1 - ----------------------------------------------------------0 AA treatment did not produce a significant increase in total phenolic content (Figure 1).…”
Section: Ascorbic Acid (Aa)mentioning
confidence: 95%